Enhancing retailer efficiency of agroindustrial product: A DEA approach based on SCOR perspective - Wike Agustin Prima Dania; Alvina Ovilia Ardiasti; Wendra Gandhatyasri Rohmah; Naila Maulidina Lu'ayya (AGROINTEK, 2025)
Retailer performance is critical for enhancing supply chain operations and achieving a competitive advantage in the food industry. It directly impacts customer satisfaction, profitability, and overall supply chain effectiveness. CV. LMN is an Indonesian apple cider drink manufacturer that involves 36 retailers in distributing its products to consumers. While the success of the marketing process relies on the retailers, the company has not previously assessed their performance. This research aims to examine CV's retailer performance. LMN using Data Envelopment Analysis from the Supply Chain Operations Reference (SCOR) perspective. The SCOR model's attributes of plan, source, deliver, and return served as the foundation for selecting evaluation factors. A CRS output-oriented DEA model was utilized to assess how efficiently retailers can increase their outputs without altering their resource consumption. The result shows that 6 out of 36 retailers are marginally efficient, indicating a potential for performance improvement and getting closer to the efficient frontier related to cash-to-cash cycle time, order received damage-free, fill rate, and customer complaints. These retailers can enhance their efficiency by implementing strategies such as reducing inventory levels, applying safety stock, negotiating payment terms with distributors, improving material handling during storage, and pre-checking products before delivery.